Comparison of yarn properties of gossypium hirsutum and naturally colored gossypium arboreum cotton - Syeda Hafsa Hassan; Tanveer Hussain; Zufiqar Ali; Habib Awais (Mehran University Research Journal of Engineering and Technology)
Naturally colored cotton can be a highly sustainable alternative to conventional cotton which entails huge consumption of water, energy, and chemicals in scouring, bleaching and dyeing. The objective of this study was to investigate the yarn properties of one of the most commonly grown Gossypium hirsutum cotton and naturally colored Gossypium arboreum cotton grown in Pakistan. Eighteen different samples of ring-spun yarn were developed using the two cotton types, in three different yarn counts (Ne 16, Ne 20, Ne 24), each with three different twist multipliers (TM: 4.00, 4.25, 4.50). Different yarn properties of all yarn samples were investigated as per standard test methods. Result comparisons show that tenacity and elongation of conventional cotton yarns was about 42% and 10 % higher as compared to that of colored cotton respectively. Similarly, hairiness, CVm and total imperfections of colored cotton yarns were 11%, 25%and 320 % higher as compared to conventional cotton respectively. Comparative analysis reveals that although yarns made from Gossypium hirsutum cotton are superior in terms of strength, elongation and uniformity. However, the properties of naturally colored Gossypium arboreum cotton yarn are good enough for making different textile products which do not require too high mechanical strength and uniformity such as knitwear, woven casuals, and home textiles like bed linen and curtains. It seems that the natural color genes of cotton suppress its strength and fiber length properties which reduced yarn tenacity, and increased yarn unevenness, imperfections, and hairiness.